An Analysis of the Regional Government Information System for Cash Management at the West Java Provincial Library and Archives Office - Anisa Rahayu; Heni Nurani Hartikayanti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The advancement of digital technology has significantly influenced the modernization of public sector financial systems, particularly in regional financial governance. In Indonesia, the Regional Government Information System (SIPD) was introduced to meet the demand for integrated, transparent, and accountable financial management. This study aims to analyze the implementation of SIPD in the cash management process at the West Java Provincial Library and Archives Service. Specifically, it investigates the application of SIPD, identifies operational challenges, and evaluates its effectiveness in supporting financial governance. A qualitative descriptive method was employed, utilizing in depth interviews, direct observations, and document analysis. The findings indicate that although SIPD has been implemented in accordance with applicable regulations, several challenges persist, such as unstable internet connectivity, inadequate user training, and limitations in system features. These limitations include the absence of data correction tools and the lack of tax integration. Such constraints reduce the system’s effectiveness and result in continued reliance on manual processes. This study emphasizes the importance of enhancing technical infrastructure and improving user competence as strategic steps to optimize the role of SIPD in strengthening regional financial performance and ensuring the quality of public financial management.